Civil Compliance and "Political Luddism": Explaining Variance in Social Unrest During Crisis in Ireland and Greece. (November 2014) - Pappas, Takis S.; O'Malley, Eoin
When badly hit by the same global financial and economic crisis in the early 2000s, the Irish and the Greek societies reacted in quite different ways. Whereas Ireland remained largely acquiescent and displayed a high degree of civil compliance, Greeks took massively to the streets using violence and attacking specifically the state and the state personnel, a phenomenon we refer to as "political Luddism." It is shown that the two countries are quite similar in terms of their economic condition, cultural background, social composition, ideological profiling, and party system dynamics, among other factors. What, then, explains the two countries' dissimilar reactions to crisis? Through a detailed analysis of the cases, the article offers evidence that the most compelling explanation relates to the varying ability of the Greek and Irish states to continue providing basic public goods and other state-related services to their respective societies.